Optimizing Concussion Care Seeking: The Influence of Previous Concussion Diagnosis Status on Baseline Assessment Outcomes. Issue 12 (October 2022) - Lynall, Robert C.; D'Lauro, Christopher; Kerr, Zachary Y.; Knight, Kristen; Kroshus, Emily; Leeds, Daniel D.; Register-Mihalik, Johna K.; McCrea, Michael; Broglio, Steven P.; McAllister, Thomas; Schmidt, Julianne D.; ,; et al.
Background: The prevalence of unreported concussions is high, and undiagnosed concussions can lead to worse postconcussion outcomes. It is not clear how those with a history of undiagnosed concussion perform on subsequent standard concussion baseline assessments. Purpose: To determine if previous concussion diagnosis status was associated with outcomes on the standard baseline concussion assessment battery. Study Design: Cross-sectional study; Level of evidence, 3. Methods: Concussion Assessment, Research, and Education (CARE) Consortium participants (N = 29, 934) self-reported concussion history with diagnosis status and completed standard baseline concussion assessments, including assessments for symptoms, mental status, balance, and neurocognition. Multiple linear regression models were used to estimate mean differences and 95% CIs among concussion history groups (no concussion history [n = 23, 037; 77.0%], all previous concussions diagnosed [n = 5315; 17.8%], ≥1 previous concussions undiagnosed [n = 1582; 5.3%]) at baseline for all outcomes except symptom severity and Brief Symptom Inventory–18 (BSI-18) score, in which negative binomial models were used to calculate incidence rate ratios (IRRs). All models were adjusted for sex, race, ethnicity, sport contact level, and concussion count. Mean differences with 95% CIs excluding 0.00 and at least a small effect size (≥0.20), and those IRRs with 95% CIs excluding 1.00 and at least a small association (IRR, ≥1.10) were considered significant. Results: The ≥1 previous concussions undiagnosed group reported significantly greater symptom severity scores (IRR, ≥1.38) and BSI-18 (IRR, ≥1.31) scores relative to the no concussion history and all previous concussions diagnosed groups. The ≥1 previous concussions undiagnosed group performed significantly worse on 6 neurocognitive assessments while performing better on only 2 compared with the no concussion history and all previous concussions diagnosed groups. There were no between-group differences on mental status or balance assessments. Conclusion: An undiagnosed concussion history was associated with worse clinical indicators at future baseline assessments. Individuals reporting ≥1 previous undiagnosed concussions exhibited worse baseline clinical indicators. This may suggest that concussion-related harm may be exacerbated when injuries are not diagnosed.